THE MORAL OF THE NATIONAL MENTALITY LIES IN ITS IMPORTANCE IN THE NATIONAL IDEOLOGY - Allayarov Xalmurat Jaqsimuratovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article presents the concept of the structural connection of the specifics of the phenomena of mentality and mentality in the framework of the development of sociospatial identity. The single root of the development of mentality and mentality as socio-cultural phenomena is revealed, functioning in various degrees of social organization, the essence of which is the need for identification as a description of the property of sociality. The socio-philosophical study of mental constructs made it possible to discover the one and the special in the process of functioning of mentality and mentality. The substantiation of their structures is given, as well as the interdependence between the structural features and characteristics of the constancy/dynamism of the mentality, as well as the mentality and significance in the development of the components of sociospatial identity: national and social identities.